Customer Focus and Business Agility on Leadership Agility for Sustainable MSME Performance - Study at Rengginang Production in Cirebon - Wike Pertiwi; Najmudin (International Journal of Management, Economic, Business and Accounting, 2023)
Purpose of the study — Description In a quickly developing business condition, a client focused reason gives everybody a genuine north to empower more prominent dexterity, Customer center gives individuals a steady establishing as they explore toward their destinations, even amidst vulnerability and flightiness. Leadership as a authority must guarantee that the lithe endeavor is really arranged to adjust to dangers and openings, that it completely uses the information and experience of pioneers at all levels, and that it conveys the qualities that are essential to its shoppers. The purpose of this study is to investigate whether leadership agility can affect the segmentation of customer focus and business agility in micro small and medium enterprise. Research method— Data were gathered from 128 responses to a questionnaire in a Rengginang of the micro small and medium enterprises (MSMEs) production. Result— The results reveal Prioritizes sustainable change, Empowers employees and teams these two types of capabilities to have an interactive effect on Customer Focus and Business Agility. Conclusion— The key contribution of this study is its examination of how leadership agility is influenced by both internal and external capabilities